Features of the Transition From a Traditional Judicial System to an Electronic Judicial System (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The global shift toward digital transformation has reached the judicial sector, where the traditional court systems are being replaced or supplemented by electronic platforms to improve efficiency and accessibility. In Uzbekistan, several presidential decrees have initiated reforms to modernize the judiciary through digitalization, aligning national practices with international standards. Despite ongoing initiatives, a comprehensive understanding of the legal, institutional, and technical implications of transitioning to electronic justice remains underdeveloped, particularly in post-Soviet legal contexts. This study aims to examine the specific features, benefits, and challenges of transitioning from a traditional judicial system to an electronic one, focusing on the Uzbek judicial framework and international practices. Findings highlight that digital courts reduce the workload of judges, cut financial expenses, and enhance the transparency and efficiency of legal proceedings. The introduction of AI, remote participation, and interoperable platforms underlines the systemic impact of informatization. The article offers a synthesized analysis of regulatory developments, technological integration, and institutional changes unique to Uzbekistan’s legal digitalization journey, while drawing comparative insights from EU digital justice strategies. A well-regulated transition to electronic justice can significantly strengthen rule of law, public trust, and judicial efficiency. However, it also necessitates continual legal adaptation and a commitment to safeguarding fairness and human rights in digital formats.